New Security and Justice Sector Partnership Models Implications of the Arab Uprisings - McNerney, Michael J. (RAND Corporation, 2014)
The United States faces a unique set of challenges and opportunities in strengthening security and justice sector partnerships in the Middle East and North Africa. RAND researchers analyzed potential new partnership models that could help implement recent policy guidance related to improving security and justice sector assistance and promoting reform in this region.